Cache replacement strategy based on content value - Dan HUANG; Rongfang SONG (Dianxin kexue)
The cache replacement mechanism is one of the important research issues of the content center network.Considering the limited cache space,the reasonable replacement of the cache content becomes a key factor affecting the overall performance of the network.Therefore,a cache replacement scheme based on content value was designed.Considering the dynamic popularity of content,the cost of caching,and the time of the most recently requested,a more realistic content value function was built,and an effective content storage and replacement scheme was designed based on the content value function.Specifically,when the cache space was insufficient,the existing cache contents were replaced according to the value from small to large.Simulation results show that compared with the traditional replacement algorithms LRU,LFU and FIFO,the proposed scheme effectively improves the content cache hit rate of network nodes and reduces the average hops of users’ content acquisition.